High-Level Thinking Skills for Middle School Students in Working on the Types of National Assessment Numeral Questions - Putri Harianti; Maimunah Maimunah; Yenita Roza (Universitas Negeri Makassar, 2022)
Assessment is an activity to reveal the quality of the process and learning outcomes. The first national assessment will be held in 2021. The type of National Assessment question used in this study is the HOTS question. This study aims to describe students' higher order thinking skills in working on types of national assessment questions. This type of research is a qualitative descriptive study, with the subject of class VIII students of SMP Negeri 2 Rambah Samo totaling 28 people. The data collection technique used was a written test consisting of 2 description questions. Based on the results of the study, students' higher order thinking skills in working on national assessment type questions were in the sufficient category, namely 42.86%, less category 17.86%, good category 32.14% and very good category 7.14%. The percentage of appearance indicators analyzed was 84.82%, followed by evaluation indicators at 58.93% and creative indicators at 24.55%. Thus, it can be seen that the high-order thinking ability of students in the very good category is still very low. So it is necessary to apply higher-order thinking skills learning in schools so that students are accustomed to working on HOTS questions and can improve students' higher-order thinking skills.